(untitled) (Global Journal of Science Frontier Research, 2015)
The child malnutrition is widely viewed in slums of Mumbai Metropolitan Region. The incidence of underweight and stunting is higher among female as compare to male. The undernourishment among children is related to parent’s education and health status. Media exposure and health care access is low among women. Most of the women are working as unskilled labors in suburbs. Child care does not exist across the slums. The women have to keep children at home, relatives or neighbors. Most of the undernourished children have cough, cold, fever and diarrhea. But few children are treated in public health care facilities. The logistic regression shows that underweight among children is negatively co-related with age, mothers normal BMI, ANC and anganwadi food. Stunting is negatively co-related to age, mother’s secondary school, per capita income, ANC, normal delivery and anganwadi food.